Über Geometrie des quasilinearischen Systems der partiellen Differentialgleichungen zweiter Ordnung - Lupeikis, Z. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: З. Ю. Лупейкис. О геометрии некоторых квазилинейных систем дифференциальных уравнений второго порядка с частными производными Z. Lupeikis. Antros eilės kvazitiesinių diferencialinių lygčių sistemų su dalinėmis išvestinėmis geometrijos klausimu